Multiwavelength Variability Analysis of the Blazar PKS 0727-11: An ~ 168 day Quasiperiodic Oscillation in the γ-Ray - Yuncai Shen; Tingfeng Yi; Vinit Dhiman; Lisheng Mao; Liang Dong (The Astrophysical Journal)
We performed variability analysis of the multiwavelength light curves (LCs) for the flat-spectrum radio quasar PKS 0727-11. Using the generalized Lomb–Scargle periodogram, we identified a possible quasiperiodic oscillation (QPO) of ~168.6 days (persisted for six cycles, with a significance of 3.8 σ ) in the γ -ray LC during the flare period (MJD 54687–55738). It is the first time that periodic variations have been detected in this source, and further supported by other methods: weighted wavelet z -transform, phase dispersion minimization, REDFIT, autoregressive integrated moving average model, and structure function analysis. Cross-correlation analysis shows that there is a strong correlation between multiband light variations, indicating that γ -ray and radio flares may originate from the same disturbance, and the distance between the emission regions of γ -ray and radio flares is calculated based on the time lag. We demonstrate that QPO arising from the non-ballistic helical jet motion driven by the orbital motion in a supermassive binary black hole is a plausible physical explanation. In this scenario, the estimated mass of the primary black hole is M ∼ 3.66 × 10 ^8 –5.79 × 10 ^9 M _⊙ .